Manajemen Risiko Pada Usaha Tempe Perspektif Hukum Ekonomi Syariah Studi Kasus Home Industry Enur Jaya Di Kampung Sukarisi Desa Sukalaksana Kecamatan Banyuresmi - Sulthonuddin, Bung Hijaj; Nafshi, Gina Shihah (STAI Al Musaddadiyah Garut, 2024)
When running a business, you are always faced with risks that might occur. Such as the various risks that occur in the Enur Jaya tempe home industry. Therefore, it is important to implement appropriate risk management to minimize losses. So a problem formulation emerges: how is risk management implemented in the tempe business in the Enur Jaya home industry? and what is the perspective of sharia economic law regarding the application of risk management in the tempe business in the Enur Jaya home industry? The objectives to be achieved from this research are to determine the application of risk management in the tempe business in the Enur Jaya home industry and to analyze the perspective of Sharia economic law regarding the application of risk management in the tempe business in the Enur Jaya home industry. The research method used by researchers is field research with a qualitative approach. Based on the results of this research, risk management in this home industry includes, among other things, not having a production target, market demand as well as managing tempeh that is not sold out, which is contrary to the principles of sharia economic law. So risk management is needed that is in accordance with sharia to minimize losses that might occur. Risk mitigation that can be done is to reprocess tempeh that has not been sold out. Keywords: Risk Management; Tempe Business; Sharia Economic;